2015
DOI: 10.1161/jaha.114.001307
|View full text |Cite
|
Sign up to set email alerts
|

Can a Novel Clinical Risk Score Improve Pneumonia Prediction in Acute Stroke Care? A UK Multicenter Cohort Study

Abstract: BackgroundPneumonia frequently complicates stroke and has a major impact on outcome. We derived and internally validated a simple clinical risk score for predicting stroke‐associated pneumonia (SAP), and compared the performance with an existing score (A2DS2).Methods and ResultsWe extracted data for patients with ischemic stroke or intracerebral hemorrhage from the Sentinel Stroke National Audit Programme multicenter UK registry. The data were randomly allocated into derivation (n=11 551) and validation (n=11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
145
4
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(173 citation statements)
references
References 30 publications
13
145
4
11
Order By: Relevance
“…Second, we also confirmed that SAP is correlated with poor outcomes in the aspects of hospitalization duration, neurological function and mortality, continued to previous study [2, 3]. We also have several limitations.…”
Section: Discussionsupporting
confidence: 87%
“…Second, we also confirmed that SAP is correlated with poor outcomes in the aspects of hospitalization duration, neurological function and mortality, continued to previous study [2, 3]. We also have several limitations.…”
Section: Discussionsupporting
confidence: 87%
“…This rate is low compared to other publications (e.g. [4]) and is probably due to the dietary recommendations of GUSS.…”
contrasting
confidence: 72%
“…Another limitation of our study is that we could not obtain reliable information about pre-stroke dependence, one of the reported risk factors of pneumonia in acute stroke [2, 1416], although we measured other important previously reported risk factors.…”
Section: Discussionmentioning
confidence: 99%